Assessment of the Effect of Micro Steel Fiber Reinforced Mortars on the Mechanical Properties of Masonry Walls - Yetkin, Musa; Calayir, Yusuf; Erkek, Hakan; Alyamac, Kursat Esat (Springer Heidelberg, 2023)
In the study, the effect of mortar type on the mechanical parameters of masonry walls was investigated. Mortar containing micro steel fiber were used as mortar type. Within the scope of the experimental study, firstly some physical and mechanical experiments were carried out for the sand, brick and mortar. Then, a total of 12 walls with dimensions of 610 x 90 x 610 mm were created for four different mortar types. The walls were subjected to the diagonal compression test. As a result of the tests, the failure patterns and the mechanical parameters such as ductility capacity, maximum shear strength, maximum displacement and failure load were obtained for walls. It was determined that the optimal wall that showed the best behavior in terms of these mechanical parameters was the wall formed with a mortar containing 2% micro steel fiber. According to the experimental results, it has been determined that the mechanical parameters of masonry walls can be improved by using micro steel fiber in the joint mortar. The optimum fiber ratio for this study was determined as 2%. For this reason, it was concluded that the fiber ratio used in the mortar should be at a certain level. Within the scope of the finite element study, finite element model was created for the optimal wall by using macro modelling technique. The Drucker Prager criterion was used for the nonlinear behavior of the wall. The effectiveness of the solutions was assessed by comparing with the experimental results.
Keywords: Masonry walls; Micro steel fiber mortar; Diagonal compression test; Nonlinear analysis; Drucker Prager criterion